MODERN APPROACHES TO DETECTING EARLY SUBCLINICAL CARDIOTOXICITY INDUCED BY CHEMOTHERAPY IN PATIENTS WITH BREAST CANCER - A. A. Avalyan; M. A. Saidova; E. V. Oshchepkova; I. Ye. Chazova (Евразийский Кардиологический Журнал)
In recent decades, developed countries of the world have made progress in the treatment of breast cancer, both because of the early detection of cancer and the use of modern methods of treatment (target therapy and chemotherapy, radiation therapy and surgical treatment). Due to this, the time of disease-free course of cancer and the duration of life of patients have increased. However, a number of antitumor drugs have cardiotoxicity [1]. It is shown that cardiovascular diseases are the second leading cause of death among women who have undergone breast cancer [27]. Reduction of systolic function of the heart is the most common manifestation of cardiotoxicity of antitumor therapy [7]. Other manifestations of cardiotoxicity include arterial hypertension (AH), acute coronary syndrome, arrhythmias and thromboses. In recent years, methods such as electrocardiography (ECG); echocardiography (EchoCG) with the classical definition of the left ventricular ejection fraction (LVEF) by the method of Simpson's biplane and the global longitudinal strain of the left ventricular (GLS) using data from the 2D Speckle Tracking Imaging; determination of the level of biomarkers of myocardial damage and magnetic resonance imaging (MRI) of the heart have been used to detect the cardiotoxicity of antitumor therapy. Thus, the early diagnosis and timely detection of cardiotoxic effects of antitumor drugs are among the tasks of cardiooncology - an area in medicine formed in recent years [1].